2004
DOI: 10.1007/s10151-004-0047-7
|View full text |Cite
|
Sign up to set email alerts
|

Duration of pneumoperitoneum on chest radiograph after open colorectal surgery

Abstract: Subdiaphragmatic pneumoperitoneum less than 20 mm high is often observed between the sixth and tenth postoperative days, without clinical importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
3
0
2
Order By: Relevance
“…Currently, there is no consensus as to what should be considered as a normal or acceptable duration of retained postoperative intraperitoneal gas, but most authors reported short durations of several days at the most, with the majority describing nearly complete disappearance of the retained gas within approximately 1 week. [1][2][3][4][5][6] Nevertheless, in cases where the finding of postoperative free intraperitoneal air is accompanied by clinical signs and symptoms such as abdominal pain, fever, leukocytosis, or peritoneal signs, prompt diagnostic and therapeutic measures should be undertaken without delay.…”
Section: Discussionmentioning
confidence: 97%
“…Currently, there is no consensus as to what should be considered as a normal or acceptable duration of retained postoperative intraperitoneal gas, but most authors reported short durations of several days at the most, with the majority describing nearly complete disappearance of the retained gas within approximately 1 week. [1][2][3][4][5][6] Nevertheless, in cases where the finding of postoperative free intraperitoneal air is accompanied by clinical signs and symptoms such as abdominal pain, fever, leukocytosis, or peritoneal signs, prompt diagnostic and therapeutic measures should be undertaken without delay.…”
Section: Discussionmentioning
confidence: 97%
“…In a study of more than 200 laparotomies, the only case associated to intestinal perforation presented a height of 2 cm of free air in the chest X-ray 6 . According with this series, the authors considered a height of 1.5 cm as the "normal" limit of postoperative pneumoperitoneum (corresponding to a "severe" classification in the Millitz's scale).…”
Section: Discussionmentioning
confidence: 99%
“…Es un método sencillo y comúnmente referido en la literatura. Algunos autores acostumbran reportar la distancia directamente en milímetros 6 , mientras que otros han establecido escalas que clasifican la cantidad de aire de acuerdo con dicha altura: ausente (0 mm), trazas (1-5 mm), leve (6-10 mm), moderado (11-15 mm) y grave (> 15 mm) 7 . Los resultados de nuestro estudio muestran que este tipo de medición puede provocar una mala interpretación del volumen residual real.…”
Section: Discussionunclassified
“…En un estudio de más de 200 laparotomías, el único caso que se asoció a perforación intestinal presentó una altura de 2 cm de aire libre en la radiografía de tórax 6 . De acuerdo con esta serie, los autores consideraron una altura de 1.5 cm como el límite «normal» de neumoperitoneo posoperatorio (correspondiente a una clasificación de «grave» en la escala de Millitz).…”
Section: Tabla 4 Ejemplo De Discrepancia Entre La Escala De Millitz Y...unclassified